2001
DOI: 10.2466/pr0.2001.89.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Aversive and Attractive Properties of Electrical Stimulation for Paramecium Caudatum

Abstract: Although there are data to show that mild electrical stimulation from a cathode source can serve as positive or attractive stimulus for paramecia, the properties of anode stimulation have not been clear. This research gives evidence to support the previously reported positive properties of cathode stimulation but showed that anode stimulation has opposite (negative or aversive) properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In a particular organism, there is no variability in the response seen to that stimulus. An example of Order 1 response is a form of taxis seen in an experiment by Armus and Montgomery (2001). They showed that paramecia approach areas in which a mild shock was delivered.…”
Section: Automatic Ordermentioning
confidence: 99%
“…In a particular organism, there is no variability in the response seen to that stimulus. An example of Order 1 response is a form of taxis seen in an experiment by Armus and Montgomery (2001). They showed that paramecia approach areas in which a mild shock was delivered.…”
Section: Automatic Ordermentioning
confidence: 99%
“…More recently, Armus and Montgomery (2001) found that cathode shock is attractive to paramecia and can be utilized as reward when conditioning paramecia; they also found that anode shock is aversive. It has been suggested that the attractive quality of the cathode shock is biologically driven by changes in the membrane potential of the paramecium.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 2000s a new series of investigations into paramecia behavior were completed by Armus and his associates. The first of these studies (Armus & Montgomery, 2001) found that if a weak shock, of approximately 6.5 V D.C., were delivered to a single subject located in a small glass trough of distilled water, the cathode area was attractive while the anode area was aversive to paramecia. Recently it has been suggested that the cathode shock is naturally attractive to paramecia because of a change in their membrane potentials.…”
mentioning
confidence: 99%